KONSEP WASATHIYAH DALAM BERAGAMA PERSPEKTIF HADIS NABAWI - Muhammad Hambal Shafwan (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2022)
Wasathiyah Islam is Islam that is rahmatan lil 'alamin, not Islam such as the understanding of extremists who tend to put forward a hard attitude without compromise (ifrâth), or the understanding of liberal groups who often interpret religious teachings very loosely, freely, even almost leaving the line of religious truth. tafrîth). This article aims to explore the prophetic hadiths which are the basis for being moderate in Islam, both in aqidah, worship, and muamalah. This will result in a complete understanding of true religious moderation. This research is a qualitative research through literature study. The method used in the research is the thematic method, by collecting hadith and correlating it with the object of research. The results of the study indicate that there are several hadiths that prohibit Muslims from being extreme in religion, both in aqidah, worship, and muamalah with others. Sahih hadiths that exist invite to understand and practice religion must go through the path of balance and be in the middle way so that religion seems friendly, gentle and affectionate. The principle of moderation in religion (wasathiyah) described in the nabawi hadith is the principle of al-khairiyah (being the best), al-tawazun (balance), raf'u al-haraj (removing difficulties), al-'is (being fair), and al-tasamuh (tolerant). Islam wasathiyah adalah islam yang rahmatan lil ‘alamin, bukan Islam seperti pemahaman para ekstremis yang cenderung mengedepankan sikap keras tanpa kompromi (ifrâth), atau pemahaman kelompok liberalis yang sering menginterpretasikan ajaran agama dengan sangat longgar, bebas, bahkan nyaris meninggalkan garis kebenaran agama sekalipun (tafrîth). Artikel ini bertujuan untuk menggali hadits-hadits nabawi yang menjadi dasar untuk bersikap moderat dalam beragama Islam, baik dalam beraqidah, beribadah, dan bermuamalah. Sehingga akan menghasilkan pemahaman yang utuh tentang moderasi beragama yang sesungguhnya. Penelitian ini merupakan penelitian kualitatif melalui studi pustaka. Metode yang digunakan dalam penelitian adalah metode tematik, dengan cara pengumpulan hadis dan mengorelasikan dengan objek penelitian. Hasil penelitian menunjukkan bahwa terdapat beberapa hadis yang melarang umat Islam untuk bersikap ekstrim dalam beragama baik dalam beraqidah, beribadah, dan bermuamalah dengan sesama. Hadits-hadits shahih yang ada mengajak untuk memahami dan mengamalkan agama harus melalui jalur keseimbangan dan berada di jalan tengah sehingga agama terkesan ramah, lembut dan kasih sayang. Prinsip moderasi dalam beragama (wasathiyah) yang diterangkan dalam hadis nabawi adalah prinsip al-khairiyah (menjadi yang terbaik), al-tawazun (keseimbangan), raf’u al-haraj (menghilangkan kesulitan), al-‘adalah (bersikap adil), dan al-tasamuh (toleran).